Pendampingan pembuatan Hand Sanitizer bagi masyarakat terdampak Covid 19 di Desa Pajarakan Kulon Kabupaten Probolinggo - Faruq Thohir, Umar; komar, Abdul (KHIDMAH : Jurnal Pengabdian Masyarakat, 2021)
Health products called Hand Sanitizers can kill germs and bacteria, apart from its very simple use, no need to use water, the use of hand sanitizers can be used anywhere, such as after eating, when in contact with friends, when from throwing garbage. This service activity aims to produce health products that are beneficial to the entire community as well as for the family and ourselves. In using the Method, we conduct lectures so that people understand about how to make hand sanitizers and explain their benefits. From the results of this service, it was explained that people understand how to make hand sanitizers from natural ingredients and know their functions and benefits.